RAPID AND SIMPLE DETERMINATION OF IBUPROFEN AND CAFFEINE IN FIXED-DOSE COMBINATION FORMULATIONS: APPLICATION TO DISSOLUTION STUDIES - MEDINA-LOPEZ, JOSE RAUL; SOTO-JUHA, JOAQUIN ALEXANDRO; CONTRERAS-JIMÉNEZ, JUAN MANUEL (International Journal of Applied Pharmaceutics, 2021)
Objective: To develop a UV-derivative spectrophotometric method with zero-crossing determinations for the simultaneous quantification of ibuprofen (IBU) and caffeine (CAF) in fixed-dose combination formulations (soft gelatin capsules). The proposed method was validated, and it was applied to determine the in vitro dissolution performance of IBU and CAF from a commercial formulation. Methods: The method is based on the use of the second-derivatives of the zero-order spectra and measurement at zero-crossing wavelengths. Linearity, accuracy, precision, stability, and influence of the filter were evaluated. Dissolution profiles of IBU and CAF were obtained with the USP Apparatus 2 at 100 rpm and 900 ml of 0.1 M phosphate buffer pH 7.4 as dissolution medium. Dissolution samples were treated with the proposed UV-derivative method and results were compared with data previously published. Results: The zero-crossing points for the determination of IBU and CAF were found at 235.6 nm and 218.8 nm, respectively. The method was linear in the range of 7.5-15 µg/ml for IBU and 5-25 µg/ml for CAF (R2>0.999, *P<0.05). The precision and accuracy of the method were within acceptable criteria (CV<0.99% and recovery 97.97% for IBU and CV<1.76% and recovery 99.05% for CAF). Fiberglass filters were the best option to filter samples and stability of all drugs was adequate when solutions were stored at 25 °C during 24 h. Dissolution of IBU and CAF at 60 min was 99-100% with dissolution profiles of sigmoidal S-shape. Weibull function and Logistic were the best-fit models that describe the in vitro dissolution performance of both drugs. Conclusion: The proposed UV-derivative method allows the simultaneous determination of IBU and CAF in fixed-dose combination formulations. The method generates reliable information that can be compared with published data. The proposed UV-derivative method is rapid and simple and can be easily adopted for routine analysis of IBU and CAF.